PENGALAMAN IBU HAMIL DALAM MENDAPATKAN PELAYANANANTENATAL CARE ( ANC ) DI RB TETA TAHUN 2017 - Fina Fanka (STIKes Al-Insyirah Pekanbaru, 2018)
Education is a lifelong human need. Educators are required to develop knowledge and skills in an effort to improve the quality of education, especially in the teaching and learning process. Educators must use teaching methods that can make students participate actively in the teaching and learning process such as teaching discussion methods. This study aims to determine the relationship of teaching methods of discussion with the results of learning subjects of midwifery concepts in the first semester students in Medan Healthy Midwifery Academy. This research is correlational with cross sectional research design, Purposive Sampling sampling technique is the first semester C class student amounted 58 respondents. Based on the result of statistical test, it is known that the distribution of teaching teaching method applied by lecturers has good response of 47 people (81%). While the distribution of learning result of midwifery concept subjects get the most B value of 32 people (55,2%). And result of product Moment test with level of trust (α) = 5% (0,05), the result of rhitung ¬ = 0,628 bigger than rtabel = 0,254, so hypothesis accepted